2020
DOI: 10.3390/ijerph17031001
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nanoscale Zero-Valent Iron for Remediation of Clayey Soil Contaminated with Hexavalent Chromium: Batch and Column Tests

Abstract: This study investigated the reduction of hexavalent chromium (Cr(VI)) in a clayey residual soil using nanoscale zero-valent iron (nZVI). Five different ratios between nZVI and Cr(VI) were tested in batch tests (1000/11; 1000/23; 1000/35; 1000/70, and 1000/140 mg/mg) with the soil. With the selected proportion resulting best efficiency, the column tests were conducted, with molded specimens of 5 cm in diameter and 5 cm in height, with different nZVI injection pressures (10, 30, and 100 kPa). The soil was contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The breakthrough curves of nZVI reached the plateau of < 0.04 at about 4 PV, which indicates that the mobility of nZVI in the soil column is low. The poor mobility of nZVI in soil columns has also been reported previously [56,57]. Dong et al studied the transport behavior of nZVI in saturated sand-and soil-packed columns and found that surface modification affected the transport process [58].…”
Section: Transport Of Nzvi and B-nzvi In Soil Columnsmentioning
confidence: 60%
“…The breakthrough curves of nZVI reached the plateau of < 0.04 at about 4 PV, which indicates that the mobility of nZVI in the soil column is low. The poor mobility of nZVI in soil columns has also been reported previously [56,57]. Dong et al studied the transport behavior of nZVI in saturated sand-and soil-packed columns and found that surface modification affected the transport process [58].…”
Section: Transport Of Nzvi and B-nzvi In Soil Columnsmentioning
confidence: 60%
“…They concluded that the PVP-nZVI technology was promising to remediate TCE-contaminated soil. Subsequently, Reginatto et al [65] investigated the performance of nZVI for the removal of hexavalent chromium (Cr(VI)) from clayey residual soil [65]. Five different nZVI materials to contaminant ratios were used, and three different nZVI injections pressure were applied.…”
Section: Nanoscale Zero-valent Ironmentioning
confidence: 99%
“…First of all, the reaction between nZVI and soil pollutants is very complex [103], and its remediation efficiency needs improvement [104]. Therefore, the research work on its reaction mechanism, such as the possible properties of soil itself [105], the potential impact of nZVI on soil pollutants [106], and the influence of combined application of nZVI and biotechnology on soil remediation, should be further studied.…”
Section: Future Prospective and Conclusionmentioning
confidence: 99%